Pluralism in the perspective of Semitic religions - Biyanto Biyanto (IAIN Salatiga, 2015)
This article explores the concepts of religious pluralism in the perspective ofSemitic religions: Judaism, Christianity, and Islam. As Semitic religions, thethree actually share some teaching similarities in the field of theology. But, inso a long history development, it turns out that there are some differences intheir theological teachings. The power history and politics factors have alsoinfluenced the relation between the followers of the Semitic religions. There-fore, it is important to explore deeply the concepts of pluralism in the threereligions and also the development of the thoughts about the religious plural-ism among the philosophers and theologians in each of the religion. This isdue to the fact that in this present context, all religions in this globe facesimilar problems dealing with the pluralism where one of the indicators is theoccurrence of radicalism even terrorism cases involving the followers of eachreligion. The triggering factor is that the followers of each religion are notready to live in diversity. It is due to the high amount of socio-religion-nu-anced radicalism cases that a number of thinkers from the three religions havebeen trying to reformulate the meanings of pluralism in the present contextwith the target to have some active involvements among the followers of theSemitic religions to solve the plurality problem. At present there is someawareness among the thinkers that each group of religion should not have some thoughts that they are the best, and it is only they that possess theheaven. Such a claim is growing from a group’s subjectivity. If this happens, itmeans that there is a threat to any efforts in implanting the values of pluralism.Artikel ini membahas konsep pluralisme keagamaan dalam perspektif agama-agama semitik, yakni Yahudi, Kristen, dan Islam. Sebagai agama semitik atauagama samawi, tiga agama tersebut sebenarnya memiliki kesamaan ajaran dibidang teologi. Tetapi dalam perkembangan sejarah yang begitu panjang ternyataada beberapa ajaran teologi yang berbeda. Faktor sejarah dan politik kekuasaanjuga berpengaruh terhadap hubungan pemeluk tiga agama wahyu tersebut.Karena itu penting ditelaah secara mendalam konsep pluralisme tiga agamatersebut. Juga penting dibahas perkembangan pemikiran tentang pluralismekeagamaan di kalangan filsuf dan teolog dari masing-masing agama. Sebab,dalam konteks kekinian semua agama di dunia ini menghadapi problem yangsama berkaitan dengan pluralisme. Diantara indikatornya, masih sering terjadikasus radikalisme, bahkan terorisme, yang melibatkan pemeluk masing-masingagama. Jika dlacak faktor pemicunya adalah ketidaksiapan pemeluk masing-masing agama untuk hidup dalam kemajemukan. Seiring dengan banyaknyakasus radikalisme sosial bernuansa agama itulah sejumlah pemikir dari tigaagama semitik tersebut telah berupaya untuk merumuskan kembali maknapluralisme dalam konteks kekinian. Targetnya adalah adanya keterlibatan yangaktif antarpemeluk agama semitik untuk mengatasi problem pluralitas. Kiniada kesadaran di kalangan pemikir agama-agama semitik bahwa setiap kelompoktidak dibenarkan merasa paling unggul dan menganggap kelompok lain tidakberarti. Juga tidak dibenarkan ada klaim kebenaran bahwa surga hanya milikkelompok tertentu. Klaim tersebut jelas tumbuh dari subjektifitas kelompok.Jika itu terjadi berarti ancaman terhadap usaha untuk membumikan nilai-nilai pluralisme.